Applying event history analysis to explain the diffusion of innovations in archaeological networks. (April 2019) - Amati, Viviana; Munson, Jessica; Scholnick, Jonathan; Habiba
Abstract: The simple dyadic structure of a network is the basis for studying a wide variety of entities and their relationships, as well as the outcomes of processes such as the diffusion of innovations. Here, we apply models from event history analysis and cultural evolutionary theory to investigate whether and by what means network ties facilitated the transmission of certain cultural traits in past complex societies. To illustrate the application of these models to archaeological data, we examine the spread of dynastic rituals by analyzing data collected from Classic Maya hieroglyphic inscriptions. In addition to providing a cautionary tale for the construction of archaeological networks, the results of this study highlight the compatibility of cultural evolutionary and social network approaches to investigate the spread of novel traits.